2021
DOI: 10.1002/anie.202016249
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Photoinduced Electron‐Donating Character of MoS2 in Covalently Linked Hybrids Featuring Perylenediimide

Abstract: The covalent functionalization of MoS 2 with ap erylenediimide (PDI) is reported and the study is accompanied by detailed characterization of the newly prepared MoS 2-PDI hybrid material. Covalently functionalizedM oS 2 interfacing organic photoactive species has shown electron and/or energy accepting,energy reflecting or bi-directional electron accepting features.H erein, ar ationally designed PDI, unsubstituted at the perylene core to act as electron acceptor,f orces MoS 2 to fully demonstrate for the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…During polymerization in TDCRP, the PL emission gradually produces a red shift (Figure a,b). It is known that the strong interactions between the polymer segment and two-dimensional plane could promote the transfer or energy dissipation of excitons, which thus results in the excitons coming back to the ground state with a longer PL emission (Figure c,d). Therefore, the PL result of the red shift proves the increased interactions between the polymer segment and two-dimensional plane during polymerization in TDCRP. In addition, the different polymer segments would produce different interactions with the two-dimensional plane, thereby leading to different degrees of the red shift.…”
Section: Resultsmentioning
confidence: 94%
“…During polymerization in TDCRP, the PL emission gradually produces a red shift (Figure a,b). It is known that the strong interactions between the polymer segment and two-dimensional plane could promote the transfer or energy dissipation of excitons, which thus results in the excitons coming back to the ground state with a longer PL emission (Figure c,d). Therefore, the PL result of the red shift proves the increased interactions between the polymer segment and two-dimensional plane during polymerization in TDCRP. In addition, the different polymer segments would produce different interactions with the two-dimensional plane, thereby leading to different degrees of the red shift.…”
Section: Resultsmentioning
confidence: 94%
“…a Please note that covalently linked MoS 2 -PDI conjugates fail to exhibit similar CT bands or any evidence for intercomponent ground-state electronic coupling. 22 A likely rationale is centered around the noncovalent nature of WS 2 −PDI. Here, PDIs are accommodated at positions, where the electronic interactions with WS 2 are maximized.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Similar conclusions were drawn for a previously reported covalent MoS 2 −PDI conjugate. 22 It signifies that the degree of functionalization is insufficient to significantly alter Coulomb interactions between electrons and holes within WS 2 via dielectric screening. 24 Concerning the polydispersity of the WS 2 nanosheets in lateral size and thickness, it has recently been shown that absorption spectra allow for the simultaneous quantification of the nanosheets dimensions in dispersion.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular functionalization of exfoliated MoS 2 nanosheets has gained increased interest. [1][2][3][4][5][6] In particular, chemically exfoliated MoS 2 nanosheets (ce-MoS 2 ) derived by treating the bulk semiconducting MoS 2 powder with organolithium compounds 7 are a proven candidate towards stable covalently modified nanosheets with small molecules. 6,[8][9][10] However, covalent functionalization of ce-MoS 2 nanosheets with polymers remains in its infancy.…”
mentioning
confidence: 99%